Study of acute toxicity of the drug Homeovox - I. A. Miroshkina; A. V. Sorokina; A. V. Volkova; V. V. Zabrodina; K. S. Kachalov; А. D. Zakharov; S. V. Alekseeva; A. S. Lapitskaya (LLC "Publisher OKI", 2020)
Relevance. Assessment of acute toxicity is a necessary stage of preclinical research of a tablets Homeovox homeopathic. The aim of present research is study of acute toxicity Homeovox.Methods. Homeovox was administered once orally and intraperitoneally to mice and rats in the maximum possible volumes for each of the administration methods and for each animal species, at the highest possible concentrations. Equivalent volume of 1 % starch solution was administered to animals of the control groups. Euthanasia and pathoanatomical dissection were performed 14 days after drug administration. Periods of animals intoxication with a detailed description of the observed clinical picture were registered.Results. The median fatal doses were not identified because Homeovox did not cause death of animals at introduction of the maximum allowable volumes and maximum allowable concentrations. The morphological view of the internal organs, detected during pathoanatomical dissection of all experimental animals, did not differ from that observed in control animals.Conclusion. It was determined that Homeovox at oral and intraperitoneal introduction concerns to practically non-toxic substances. According to classification Sidorov KK this homeopathic tablets may be related to 5th toxicity class. According to GOST 12.1.007-76 Homeovox may be related to 4th danger class.